Benchmark Performance of Global Switching versus Local Switching for Trajectory Surface Hopping Molecular Dynamics Simulation: Cis↔Trans Azobenzene Photoisomerization. Issue 10 (31st March 2017) - Yue, Ling; Yu, Le; Xu, Chao; Lei, Yibo; Liu, Yajun; Zhu, Chaoyuan
Abstract: A newly developed global switching algorithm that does not require calculation of nonadiabatic coupling vectors reduces computational costs significantly. However, the accuracy of this simplest nonadiabatic molecular dynamic method has not been extensively compared with the conventional Tully's fewest switches. It is necessary to demonstrate the accuracy of this global switching algorithm. An extensive comparison between local and global switching on‐the‐fly trajectory surface hopping molecular dynamics is performed for cis ‐to‐ trans (800 sampling trajectories) and trans ‐to‐ cis (600 sampling trajectories) azobenzene photoisomerization at the OM2/MRCI level. The global switching algorithm is coded into the Newton‐X program package. Excellent agreement between the two switching algorithms is obtained not only for highly averaged quantities of quantum yields and lifetimes, but also for detailed contour patterns of product distributions, hopping spot distributions and hopping directions in terms of conical intersections between ground and the first excited states. Therefore, the global switching trajectory surface hopping method can be applied to larger complex systems in which nonadiabatic coupling is not available for excited‐state molecular dynamic simulations. Abstract : Make the switch : A global switching method is demonstrated to be as accurate as local switching in Tully's fewest switching method for describing the isomerization of azobenzene. The present method is therefore a useful tool in excited‐state nonadiabatic molecular dynamics simulations of large systems in which nonadiabatic couplings are usually unavailable for most quantum chemistry methods. The present method is coded into the Newton‐X platform.